DINAMIKA PENERAPAN STANDAR PENGELOLAAN PADA PERENCANAAN, PELAKSANAAN, DAN PENGAWASAN PENDIDIKAN DI SDN WADAS IV TELUK JAMBE KARAWANG - Ahmad Nurfalah; Yusriya Ni'matul 'Izzah; Denissa Aulia Ramadhani; Ajeng Nova Saputri; Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the practice of educational management standards during planning, implementation and supervision at SDN Wadas IV, a public primary school located in Teluk Jambe, Karawang. The study employed the study applied a a qualitative descriptive design employing a case study framework, relying on interviews, observations, and field notes as procedures for data collection. Data were analyzed through according to Miles and Huberman’s interactive framework, the process entails data condensation, presentation, and the formulation of conclusions. The credibility of the findings was ensured through triangulation of sources and methods, along with member checking with participants. Results show that school planning was carried out through the preparation of the School’s Strategic Work Plan (RKS) along with the School Budget and Activity Plan (RKAS), which serve as the school’s planning and budgeting instruments both developed in a structured and participatory manner. Program implementation was reinforced by the principal’s leadership, which fostered collaboration with teachers. Meanwhile, supervision took the form of regular developmental activities that contributed in order to improve teaching quality. The uniqueness of this research lies in exploring and mapping the contributing factors, challenges, and managerial strategies of a rural primary school context, which has rarely been addressed in previous research. These findings provide practical implications for principals, teachers, and policymakers in strengthening school governance, while also offering a reference for other primary schools facing similar conditions.